Global warming and cities. Increasing vegetation and urban planning between the unfinished and the urban landscape - Andrea Sciascia (Agathón)
The paper focuses on the relationship between urban planning and global warming mitigation strategies by constructing an argument that, starting from the legacy of the Modern Movement, includes the outcomes of more recent research. The thesis founded on the increase of vegetation in urban areas as an indispensable tool for temperature mitigation emerges as the protagonist from this scientific starting point. In the course of this in-depth study, this proposal finds an experimental verification through some concrete design experiences that combine the environmental objective while taking care of the quality of living spaces. The projects demonstrate how the twofold objective (containment of global warming and quality of living spaces) remains constant regardless of the scales of intervention, testifying to an overall cultural transformation that takes shape from interior architecture to the territory.